2015
DOI: 10.1038/nature14483
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lymphatics are heterogeneous in origin and respond to injury

Abstract: The lymphatic vasculature is a blind-ended network crucial for tissue fluid homeostasis, immune surveillance and lipid absorption from the gut. Recent evidence has proposed an entirely venous-derived mammalian lymphatic system. In contrast, we reveal here that cardiac lymphatic vessels have a heterogeneous cellular origin, whereby formation of at least part of the cardiac lymphatic network is independent of sprouting from veins. Multiple cre-lox based lineage tracing revealed a potential contribution from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
587
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(629 citation statements)
references
References 51 publications
(60 reference statements)
18
587
3
2
Order By: Relevance
“…Lymphangiogenesis occurs after MI 35. Enhancement of lymphangiogenesis may reduce myocardial oedema and cardiac fibrosis, promoting improvement in cardiac function 36, 37. Our data show that lymphatic capillaries in the infarcted heart increased in cell patch group than that in patch‐ or MSC‐only groups.…”
Section: Discussionmentioning
confidence: 65%
“…Lymphangiogenesis occurs after MI 35. Enhancement of lymphangiogenesis may reduce myocardial oedema and cardiac fibrosis, promoting improvement in cardiac function 36, 37. Our data show that lymphatic capillaries in the infarcted heart increased in cell patch group than that in patch‐ or MSC‐only groups.…”
Section: Discussionmentioning
confidence: 65%
“…3a). This is consistent with recently published data showing Pdgfrb‐Cre mediated targeting of ECs within the cardinal vein, JLS and lymphovenous valves (Turner et al, 2014), but is in contrast to findings of Klotz et al ., (2015) reporting absence of Pdgfrb‐Cre mediated recombination within the E10 cardinal vein and E12.5 JLS (Klotz et al, 2015). FACS analysis of endothelial cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We (Stanczuk et al ., 2015) and others (Klotz et al ., 2015) recently showed that Pdgfrb‐Cre unexpectedly also targets a large proportion of embryonic lymphatic endothelial cells (LECs) in the developing mesentery (Stanczuk et al ., 2015) and the heart (Klotz et al ., 2015). These observations were made in the context of the startling discovery that LECs in the heart (Klotz et al ., 2015), mesentery (Stanczuk et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations